2022
DOI: 10.3389/fendo.2022.960682
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive iodine in low- to intermediate-risk papillary thyroid cancer

Abstract: It remains controversial whether papillary thyroid cancer (PTC) patients with low- to intermediate-risk disease should receive radioactive iodine (RAI) after total thyroidectomy (TT). We aim to identify those who might benefit from RAI treatment in PTC patients with cervical nodal metastasis after TT. Patients were divided into TT and TT+RAI groups from the Surveillance, Epidemiology, and End Results (SEER) database (2004–2018). Overall survival (OS) and cancer-specific survival (CSS) were compared, and propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These results were consistent with another registry‐based study which used propensity score matching to account for differences in clinicopathologic characteristics between the RAI and NOI groups. They reported that NOI follow‐up was associated with poorer OS compared with postoperative RAI therapy (HR 1.52, 95% CI, 1.11–2.07) in intermediate‐risk PTC 32 . Additionally, Wang et al also reported that RAI therapy improves DSS in intermediate‐risk PTC (adjusted HR = 0.65, 95% CI, 0.46–0.93, p = .017), particularly in male patients, age ≥45 years and primary tumour size >2 cm 6 .…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with another registry‐based study which used propensity score matching to account for differences in clinicopathologic characteristics between the RAI and NOI groups. They reported that NOI follow‐up was associated with poorer OS compared with postoperative RAI therapy (HR 1.52, 95% CI, 1.11–2.07) in intermediate‐risk PTC 32 . Additionally, Wang et al also reported that RAI therapy improves DSS in intermediate‐risk PTC (adjusted HR = 0.65, 95% CI, 0.46–0.93, p = .017), particularly in male patients, age ≥45 years and primary tumour size >2 cm 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The goal of surgery is to remove the primary tumor and any involved lymph nodes while minimizing the risk of recurrence. Following thyroidectomy, RAI therapy may be recommended for certain PTC patients, particularly those with high-risk features such as larger tumors, angioinvasion presents, lymph node involvement, or distant metastasis ( 24 ). RAI therapy involves the administration of a radioactive iodine isotope (iodine-131) that selectively targets and destroys any remaining thyroid tissue or cancer cells.…”
Section: Clinical Management Of Ptcmentioning
confidence: 99%